1983
DOI: 10.1093/rheumatology/22.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic Reactions to Piroxicam, Naproxen and Tiaprofenic Acid

Abstract: Photosensitivity investigations have been carried out using an irradiation monochromator on 31 patients taking one of seven different nonsteroidal anti-inflammatory agents for the treatment of rheumatoid and osteoarthritis. Six patients, who were taking either piroxicam, naproxen or tiaprofenic acid, experienced adverse immediate reactions of erythema and flaring, together with an urticarial response in four of these six patients. No phototoxic response was observed in patients taking either indomethacin, keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…2 We have recently found that photodecarboxylation of 6-methoxya-methyl-2-naphthaleneacetic acid (naproxen, 1H; Scheme I) leads to products derived from a carbenium ion (V),' whose formation can be explained by homolysis of a radical cation (111) a h r photoionization. This new photodecarboxylation pathway is interesting in connection with the mechanisms currently accepted for one-electron oxidation of carboxylates and also as a photochemical key to explain the observed in vivo phototoxicity exhibited by naproxen, 4.6 a property shared by other nonsteroidal anti-inflammatory drugs of the same structural group. 616 We studied the oxidative decarboxylation of naproxen as an alternative method of drug degradation.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…2 We have recently found that photodecarboxylation of 6-methoxya-methyl-2-naphthaleneacetic acid (naproxen, 1H; Scheme I) leads to products derived from a carbenium ion (V),' whose formation can be explained by homolysis of a radical cation (111) a h r photoionization. This new photodecarboxylation pathway is interesting in connection with the mechanisms currently accepted for one-electron oxidation of carboxylates and also as a photochemical key to explain the observed in vivo phototoxicity exhibited by naproxen, 4.6 a property shared by other nonsteroidal anti-inflammatory drugs of the same structural group. 616 We studied the oxidative decarboxylation of naproxen as an alternative method of drug degradation.…”
mentioning
confidence: 92%
“…[2][3][4][5][6][7][8] Inner-sphere mechanisms also have been proposed for some oxidations with metal ions. 1g We compared the oxidation of naproxen and that of its salt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical setting, the use of phototoxic drugs prevents patients from going outdoors during daytime, because these drugs are excited by exposure to sunlight and cause toxic reactions, resulting in erythema and edema (Diffey et al, 1983). Additionally, since the treatment of some skin diseases requires ultraviolet irradiation (Parrish et al, 1974), use of phototoxic drugs prevents patients from being given such treatments.…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the oxicams group of chemicals, which have the 1,2-thiazine 1,1-dioxide as a main nucleus fused with either benzene or heterocycles ring systems. Shortly after the PRX became widely available for the therapeutic use it was associated with development of adverse light-induced biological effects, which were demonstrated mainly as a phototoxicity [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%